Did the Communication Barriers During the Lockdown Reduce Students’ Satisfaction? - Li, Juan; Li, Sitan; Hu, Jianbo; Zhong, Caixia; Liu, Pan (Frontiers in Education, 2022)
The lockdown control measures implemented against the pandemic of COVID-19 have had a global effect on various aspects of our lives as a society. Considering the impact of the lockdown caused by COVID-19 on adolescents, we conducted practical longitudinal research on the changes in adolescent satisfaction before and after lockdown. A total of 221 students aged 13-19 years from a professional adolescent football school in China participated in a self-report satisfaction questionnaire before and after the lockdown. The results showed that the satisfaction of adolescents improved significantly after the lockdown. There were significant differences based on age in the improvement rate, but the correlation between the students’ home regions (and how they were affected by COVID-19) and satisfaction improvement was not significant. To examine the possible reasons behind the improvement in adolescent satisfaction, we then analyzed in detail the online teaching and training methods implemented by the school during the lockdown. Based on this investigation, we outlined recommendations to guide future practice. This research is expected to deepen the theory and practice associated with the development of Chinese adolescent teaching, which may be applied to other training institutions.